Music Education in Portugal during the First Republic (1910-1926) - Borralhinho, Bruno (Historia y Memoria de la Educación, 2018)
The republican movement erupted in Portugal in the last decades of the nineteenth century, probably driven by a natural assimilation —although late in comparison with other European countries— of the values that followed the Ancien Régime, but above all by the exhaustion of the bipartisan system of the Portuguese constitutional monarchy. The crown tried to contain the political instability with authoritarian governmental solutions, but the regicide of 1908 in which the king D. Carlos and the crown prince Luís Filipe were murdered ended up being an omen of the fall of the monarchy two years later. On October 5, 1910 the republican revolution triumphed, not surprisingly, and the country experienced a series of important social and political transformations. In many cases the revolution did not represent a sudden break with the past but rather the confirmation of a new phase of transition and transformation of Portuguese society, especially in the cultural and artistic field. The music sector —this article refers exclusively to classical music, commonly known as western vocal and instrumental music, excluding parallel sectors such as electronic music or jazz, for example— was not alien to these transformations. This text investigates some paradigmatic cases of the new and effervescent climate of the First Republic, revealing a certain instability and incoherence of a period more distinguished by its expectations than by its achievements.